Ant species but not trait diversity increases at the edges: insights from a micro‐scale gradient in a semi‐natural Mediterranean ecosystem. (14th February 2021) - Frasconi Wendt, Clara; Frizzi, Filippo; Aiello, Giulia; Balzani, Paride; Santini, Giacomo
Abstract : 1. Different habitat types are generally associated with shifts in ant species and traits, and even along a micro‐scale woodland–grassland gradient, ant biodiversity may change at the edge proximities as a result of abiotic alterations. However, to the best of authors' knowledge, the changes in ant diversity along this type of gradient are understudied, especially from a functional perspective. 2. The authors sampled ant species in eight micro‐scale woodland–grassland gradients in a Mediterranean ecosystem, each comprising 16 m, to assess how ant species diversity, community composition, functional structure, and single‐ and multi‐trait functional diversity change at the edge and in the two adjacent habitats (woodland and grassland) as the distance from the edge increases. 3. No differences in species richness, species diversity, and community composition were found within the woodland and grassland habitats. Distance from the edge into the adjacent habitats explained changes in functional structure and diversity, which mainly increased in the grassland habitat; body length, leg length, sugar‐based diet, dominant behaviour, and multi‐trait diversity increased in the grassland. Along the micro‐scale gradient, edges showed the highest species diversity and community composition that resulted from the overlap of the communities from the adjacent habitats. 4. This study shed light on changes in ant species and traits along a micro‐scale woodland–grassland gradient, and it highlights the importance of integrating different diversity approaches (functional and taxonomic) at a micro‐spatial scale. Abstract : x Ant species diversity, but not richness, changed along the woodland–grassland gradient. Ant functional diversity increased in the grassland habitat. Ant community composition from the grassland and woodland habitats overlapped at the edges.